Density–stiffness scaling in minerals upon disordering: Irradiation vs. vitrification. (March 2019) - Krishnan, N. M. Anoop; Ravinder, R.; Kumar, Rajesh; Le Pape, Yann; Sant, Gaurav; Bauchy, Mathieu
Abstract: When subjected to irradiation or vitrification, minerals become disordered at the atomic scale, which, in turn, affect their density and stiffness. However, the nature of the relationship between structural disorder, density, and stiffness remains poorly understood. Here, based on molecular dynamics simulations, we investigate the effect of irradiation- and vitrification-induced disordering in a series of silicate minerals. We show that irradiation- and vitrification-induced disordering yield comparable, yet not fully equivalent variations in density and stiffness. Interestingly, we report the existence of a power law density–stiffness scaling exhibiting a scaling exponent that is similar to that observed in porous assembled cellular materials. Graphical abstract: Image 1